Insight into the interaction between hydrogen bonds in brown coal and water. (15th January 2019) - Han, Yanna; Liao, Junjie; Li, Wen; Ma, Hong; Bai, Zongqing
Graphical abstract: Highlights: D2 O was used innovationally instead of H2 O to interact with brown coal. OH–π and COOH dimer of dried brown coal are disrupted by re-adsorbed water. Remaining water is hydrogen-bonded to Ar–OH and COOH as drying temperature increasing. Ar–OH and COOH are obtained from the scission of cyclic OH tetramer, OH–ether and COOH dimer. IR peak positions of COD bonds formed by D2 O bonded to Ar–OH and COOH are found to be 2575 and 2490 cm −1, respectively. Abstract: The hydrogen bonds between water and oxygen-containing functional groups are key factors controlling water re-adsorption and drying behaviour of brown coal. However, the changes of hydrogen bonds are hard to investigate because of the overlap of H2 O IR vibration bands with those due to coal hydrogen bonds. Thus, D2 O was innovationally used instead of H2 O to interact with brown coal. The interaction between re-adsorbed water and the hydrogen bonds of brown coal was investigated by studying the IR spectra changes and the release of D2 O, HDO, H2 O and CO2 during drying of brown coals containing adsorbed D2 O. The Gibbs free energies of reactions involving hydrogen bonds were calculated to complement the findings of IR measurements. The effect of re-adsorbed water on hydrogen bonds of brown coal and the interaction among them during drying process were revealed for the first time. The results show that the OH–π and COOH dimer hydrogen bonds in dried brown coal are easily disrupted by re-adsorbed water. During the brown coal drying process, the re-adsorbed water cannot be completely removed, but some of it participates in the rearrangement of hydrogen bonds. The remaining re-adsorbed water is hydrogen-bonded to the free OH and free COOH groups at higher temperature. The free OH groups are obtained from the decomposition of cyclic OH tetramer and OH–ether hydrogen bonds, and the free COOH groups from the disruption of COOH dimer disrupted by re-adsorbed water. The self-associated n-mers (n > 3) and OH–N hydrogen bonds are formed during the brown coal drying process. The infrared peak positions of COD bonds formed by D2 O molecules bonded to free OH groups and free COOH groups are found to be 2575 and 2490 cm −1, respectively. Some O–D bonds remain intact at temperatures as high as 330 °C. Thus in situ DRIFT spectrum analysis combined with isotopic substitution provides a rapid and direct method for research on water behaviour in brown coal.